High Prevalence of Human-Associated Escherichia coli in Wetlands Located in Eastern France - Martak, Daniel; Henriot, Charles P.; Broussier, Marion; Couchoud, Charlotte; Valot, Benoit; Richard, Marion; Couchot, Julie; Bornette, Gudrun; Hocquet, Didier; Bertrand, Xavier (Frontiers in Microbiology, 2020)
Escherichia coli that are present in the rivers are mostly brought by human and animal faeces. Contamination occurs mostly through wastewater treatment plant (WWTP) outflows and field amendment with sewage sludge or manure. However, the survival of these isolates in river-associated wetlands remains unknown. Here, we assessed E. coli population structure in low-anthropized wetlands located along three floodplains to identify the major source of contamination of wetlands, whose functioning is different from the rivers. We retrieved 179 E. coli in water samples collected monthly from 19 sites located in eastern France over one year. Phylogroups B1 and B2 were dominant in the E. coli population, while phylogroup A was dominant in isolates resistant to third-generation cephalosporins, which harboured the extended-spectrum -lactamase encoding genes blaTX-M-15 and blaCTX-M-27 in half of the cases. The high proportion of isolates from human source can be attributed to WWTP outflows and the spread of sewage sludge. We analysed the distribution of the isolates belonging to the most human-associated phylogroups (B2 and D) on a phylogenetic tree of the whole species and compared it with that of isolates retrieved from patients and from WWTP outflows. The distribution of the three E. coli populations was similar, suggesting the absence of a specific population in the environment. Our results suggest that a high proportion of E. coli isolates that reach and survive low-anthropized environments such as wetlands are from human source. To the best of our knowledge, this is the first study assessing E. coli contamination and resistance genes in natural freshwater wetlands.